Odontogenic Tumors in Children and Adolescents: A Retrospective Analysis at a Tertiary-Level Health Care Facility in Bangladesh - Ismat Ara Haider; A F M Shakilur Rahman; Md Imrul Hasan; Md Sakawath Hosain Shah; Sukanta Kumar Roy; Soroar Jahan Towhid (Update Dental College, 2024)
Introduction: This study presents the oral and maxillofacial pathological features of several types of odontogenic tumors in children and adolescents less than 18 years of age from a Bangladeshi tertiary-level healthcare facility. Materials and Methods: In this retrospective cross-sectional study, the World Health Organization (WHO) categorization for head and neck tumors in 2022 was used to assess the frequency of odontogenic tumors in children and adolescents. Data relating to sex, age, and tumor site were retrieved and presented. The Chi-square test was implemented to study the association between gender, age, and site with different types of odontogenic tumors. Results: A total of 106 cases were found, and all the cases were benign. Ameloblatoma (75.47%) was the most common tumor, followed by odontogenic myxoma (9.44%), cemento-ossifying fibroma (5.66%), and odontoma (4.72%). A male (60.38%) predominance was observed in the gender distribution, but no statistically noteworthy (P = 0.43) relationship was found. Most of the cases were found in the 13-18 age group (63.21%), with a mean age (standard deviation) of 13.01 (2.29) years. There was no statistical significance found between age group and tumor type (P = 0.78). The mandibular (95.28%) predominance was found over the maxilla (4.72%) (Mandible: Maxilla = 20.2:1) and was statistically significant (P= 0.002). In the mandible, the posterior region (88.68%) was mostly affected. Conclusions: Early detection of odontogenic tumors is rare, and as people aged, they become more common. Ameloblatoma was the most prevalent odontogenic tumor in the jaws, followed by odontogenic myxoma, cemento-ossifying fibroma, and odontoma. Adolescents experience odontogenic tumors more frequently than children do. The mandible was observed to predominate over the maxilla in terms of site distribution. The mandible's posterior portion was primarily affected. Update Dent. Coll. j: 2024; 14(1):19-23